Managing public-private strategic alliances - Das, T. K. 1938- (Research in strategic alliances., 2014)
Managing Public-Private Strategic Alliances is a volume in the book series Research in Strategic Alliances that focuses on providing a robust and comprehensive forum for new scholarship in the field of strategic alliances. In particular, the books in the series cover new views of interdisciplinary theoretical frameworks and models, significant practical problems of alliance organization and management, and emerging areas of inquiry. The series also includes comprehensive empirical studies of selected segments of business, economic, industrial, government, and non-profit activities with wide prevalence of strategic alliances. Through the ongoing release of focused topical titles, this book series seeks to disseminate theoretical insights and practical management information that should enable interested professionals to gain a rigorous and comprehensive understanding of the field of strategic alliances.Managing Public-Private Strategic Alliances contains contributions by leading scholars in the field of strategic alliance research. The chapters in this volume cover a number of significant topics that speak to the critical issues in managing strategic alliances involving public-private enterprises in various industries and countries. The topics cover both the broader issues, such as contracting and bundling public sector infrastructure and services, formation of innovation alliances and alliance portfolios, and competing institutional logics in public-private alliances, and the more focused problems of trust-building, sustainability-oriented co-innovation, and organizational justice in multipartner alliances. The chapters include empirical as well as conceptual treatments of the selected topics, and collectively present a wide-ranging review of the noteworthy research perspectives on managing public-private strategic alliances.